2004
DOI: 10.1080/03079450400013220
|View full text |Cite
|
Sign up to set email alerts
|

Hatchability, serology and virus excretion followingin ovovaccination of chickens with an avian metapneumovirus vaccine

Abstract: The present investigation describes for the first time the effect of an avian metapneumovirus vaccine administered in ovo to 18-day-old chicken embryos. The application of the vaccine had no adverse effect on the hatchability or the health of the chicks post hatch. The antibody titres achieved were higher than those determined for birds vaccinated at 1 day old. Not only were the mean titres in the in ovo vaccinated groups higher, but many more birds developed a measurable antibody response than birds vaccinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 16 publications
2
0
0
Order By: Relevance
“…SPF embryos were inoculated with graded doses of 11/94 vaccine in ovo or with a high vaccine dose at day old to compare the aMPV-specific serological immune response induced by these vaccination routes. At 22 days of age all of the in ovo vaccinations, including 1000 fold less virus than given at day old, gave significantly better responses than day old vaccination with 10 4.5 TCID 50 (10 1.5 TCID 50 in ovo versus 10 4.5 TCID 50 at day old, p=0.00006) (figure 1) confirming previous results (Hess et al, 2004). Furthermore, 100% of the birds vaccinated in ovo with 10 4.5 TCID 50 had seroconverted after 22 days, whereas only 60% of the birds vaccinated at day old had seroconverted.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…SPF embryos were inoculated with graded doses of 11/94 vaccine in ovo or with a high vaccine dose at day old to compare the aMPV-specific serological immune response induced by these vaccination routes. At 22 days of age all of the in ovo vaccinations, including 1000 fold less virus than given at day old, gave significantly better responses than day old vaccination with 10 4.5 TCID 50 (10 1.5 TCID 50 in ovo versus 10 4.5 TCID 50 at day old, p=0.00006) (figure 1) confirming previous results (Hess et al, 2004). Furthermore, 100% of the birds vaccinated in ovo with 10 4.5 TCID 50 had seroconverted after 22 days, whereas only 60% of the birds vaccinated at day old had seroconverted.…”
Section: Resultssupporting
confidence: 88%
“…With the rapid spread of disease through an aMPV infected flock an early onset of immunity could bring significant advantages to the poultry industry. We found that in ovo vaccination of SPF chicken embryos induced a significantly higher antibody response to aMPV than day old vaccination of chicks confirming previous results (Hess et al, 2004). However, a similar difference in the serological response was not observed when vaccinating MDA positive chick embryos as has been demonstrated for turkeys (Worthington et al, 2003).…”
Section: Discussionsupporting
confidence: 91%